Atomic Assurance : The Alliance Politics of Nuclear Proliferation - Lanoszka, Alexander (Book collections on Project MUSE., 2018)
"This book looks at what makes alliances so credible as to prevent nuclear proliferation, how alliances can break down and encourage nuclear proliferation, and whether security guarantors like the United States can use their alliance ties to end the nuclear efforts of their allies"--